Identifikation von Merkmalen psychisch stark beanspruchter Beschäftigter in kleinen und mittelständischen Unternehmen - Voss, Amanda Sophie; Amler, Nadja; Wischlitzki, Elisabeth; Drexler, Hans (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2019)
Objective: The psychosocial risk assessment should contribute to keeping work-related influences on employees at a low level and avoiding stress. Whether or not mental stress places undue mental strain on employees depends, amongst other things, on their individual requirements. The objective of this work is to identify characteristics of employee groups subject to high levels of mental stress as a basis for targeted measures in workplace health promotion and prevention. Method: A questionnaire was used to collect data on mental stress and strain from n = 1280 employees in 12 small and medium-sized enterprises (SMEs). A subgroup with a higher level of mental strain and a subgroup with a lower level of mental strain were identified by means of a hierarchical cluster analysis. The two groups were then compared in terms of differences in mental stress and resources. Results: Various factors such as pressure of work, lack of resources and health problems occur simultaneously in the cluster with a higher level of mental strain, which are in the end accompanied by a worse global assessment of the workplace. Men and persons over the age of 50 have a greater tendency to be in the high-strain group. With regard to the areas that typically cause mental stress, the group subject to strain report the highest/most frequent pressures in the area of “work organisation”, in particular for work under time pressure and work interruptions. In terms of resources, there are only small effects with consistently significant differences. Conclusions: The results confirm the preferred approach of WHM, which is to implement measures focusing on working conditions, and at the same time underline the importance of behavioural strategies. Employers should take into account that some employees are more sensitive to working conditions than others. A healthy corporate culture with a holistic WHM system and an attentive company medical officer should always have their specific needs in mind in order to keep them healthy and efficient for as long as possible.
CRIS-Team Scopus Importer:2019-06-21
Keywords: Mental strain; Psychosocial risk assessment; SME; Workplace health management